Intermittent Hypoxia Training Prevents Deficient Learning-Memory Behavior in Mice Modeling Alzheimer's Disease: A Pilot Study - Myoung-Gwi Ryou; Xiaoan Chen; Xiaoan Chen; Ming Cai; Ming Cai; Hong Wang; Hong Wang; Marianna E. Jung; Daniel B. Metzger; Robert T. Mallet; Xiangrong Shi (Frontiers in Aging Neuroscience, 2021)
In mouse models of Alzheimer's disease (AD), normobaric intermittent hypoxia training (IHT) can preserve neurobehavioral function when applied before deficits develop, but IHT's effectiveness after onset of amyloid-β (Aβ) accumulation is unclear. This study tested the hypothesis that IHT improves learning-memory behavior, diminishes Aβ accumulation in cerebral cortex and hippocampus, and enhances cerebrocortical contents of the neuroprotective trophic factors erythropoietin and brain-derived neurotrophic factor (BDNF) in mice manifesting AD traits. Twelve-month-old female 3xTg-AD mice were assigned to untreated 3xTg-AD (n = 6), AD+IHT (n = 6), and AD+sham-IHT (n = 6) groups; 8 untreated wild-type (WT) mice also were studied. AD+IHT mice alternately breathed 10% O2 for 6 min and room air for 4 min, 10 cycles/day for 21 days; AD+sham-IHT mice breathed room air. Spatial learning-memory was assessed by Morris water maze. Cerebrocortical and hippocampal Aβ40 and Aβ42 contents were determined by ELISA, and cerebrocortical erythropoietin and BDNF were analyzed by immunoblotting and ELISA. The significance of time (12 vs. 12 months + 21 days) and treatment (IHT vs. sham-IHT) was evaluated by two-factor ANOVA. The change in swimming distance to find the water maze platform after 21 d IHT (−1.6 ± 1.8 m) differed from that after sham-IHT (+5.8 ± 2.6 m). Cerebrocortical and hippocampal Aβ42 contents were greater in 3xTg-AD than WT mice, but neither time nor treatment significantly affected Aβ40 or Aβ42 contents in the 3xTg-AD mice. Cerebrocortical erythropoietin and BDNF contents increased appreciably after IHT as compared to untreated 3xTg-AD and AD+sham-IHT mice. In conclusion, moderate, normobaric IHT prevented spatial learning-memory decline and restored cerebrocortical erythropoietin and BDNF contents despite ongoing Aβ accumulation in 3xTg-AD mice.